Pengaruh Kepuasan terhadap Loyalitas Pelanggan dengan variabel Variety Seeking sebagai Variabel Moderasi (Studi Kasus Pengguna Kartu Axis di Kota Padang) - Leni Gustina; Ullya Rahmi Aswin; Fitrah Sari (CV. ITTC INDONESIA, 2022)
Customer loyalty means a customer's commitment to a brand, store, and supplier, and is based on a very positive attitude from customers and is reflected in their positive purchasing behavior. This research aims to analyze the influence of satisfaction on user loyalty with the tendency to seek variety as a moderating variable. This research is quantitative research using survey methods. The sampling method used was a purposive sampling method by taking data from 100 Axis cellular card users in the city of Padang. The analytical method used in this research is multiple regression analysis and moderated regression analysis. The research results show 1) Satisfaction has a positive influence on customer loyalty, 2) Variety seeking has a positive influence on customer loyalty and 3) Satisfaction has a positive influence on customer loyalty with variety seeking as a moderating variable. The research implications show that the Axis mobile card provider company must design an effective marketing program to maintain customer loyalty. Keyword : satisfaction, customer loyalty, tendency to seek variety